[en] CORPORATE BONDS ANALYSIS: THE CASE OF PETROBRAS USD 11 BILLION BONDS ISSUE THE BIGGEST FOR EMERGING MARKETS - MAURÍCIO PIRAGIBE DE CARVALHO FARIA (MAXWELL, 2015)
[pt] Este trabalho analisará uma das maiores emissões de bonds de todos os tempos, a emissão de USD 11 bilhões de bonds da Petrobras que aconteceu em maio de 2013. Além de ser a maior transação da história para países emergentes até hoje, a emissão também foi feita em hora oportuna quando a Petrobras aproveitou uma excelente janela e mercado para fazer a emissão. A repercussão da transação também foi excelente tendo sido veiculada em vários meios de comunicação. O trabalho relatará do anúncio, precificação e lançamento da emissão que foi muito bem recebida pelo mercado financeiro. === [en] This paper will examine one of the largest bond issue ever, the USD 11 billion Petrobras bonds issue by Petrobras, the brazilian oil company, held in May 2013. Besides being the largest transaction in history for emerging countries until today, the issue has also been taken in proper time when Petrobras took an excellent market window to make the issue. The effect of the transaction was also great having been conveyed in various media vehicles. The work will speak with the market s announce, pricing and launch the issue which was very well received by the financial market.